PENILAIAN FORMATIF PESERTA DIDIK ATAS KOMPETENSI PENDIDIK DALAM PROSES PEMBELAJARAN - Jusuf Blegur; M. Rambu P. Wasak; Lukas Manu (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2017)
This study aims to assess teachers’ competence in learning process. Research used is quantitative approach designed descriptively. The research paticipant are 76 studens determined by proportional stratified random sampling technique (class A to F). The data for teaching competency were collected using questionnaire developed by the Ministry of Education and Culture (2015), involving 28 closed-statements with Likert scale model. The questionnaire was responded on a scale of 5 to 1 (very good/very high/always up to not good/very low/never). All data is processed by descriptive analysis using SPSS 20.00 for windows. The result is that the 9 courses which are assessed formatively by the participants indicated that the teaching competence is in the very high category (69%) so that it needs to be maintained and developed continuously.